EXAMINING THE RELATIONS BETWEEN EMPLOYEES’ PERCEPTION OF CORPORATE SOCIAL RESPONSIBILITY, CUSTOMER ORIENTATION AND PERCEIVED PERFORMANCE - Ebru Enginkaya; Gizem Köse (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In today's conditions, almost all businesses, of regardless of the sector they operate in, use social responsibility effectively to gain competitive advantage. Researches on corporate social responsibility commonly centered on customers’ perception, while investigating employees’ point of view is still needed. This research investigates relations between employee perceptions of corporate social responsibility, customer orientation, and perceived performance. Data were obtained from 218 employees and analyzed by Partial Least Squares (PLS) Structural Equation Modelling technique. Results show that all dimensions of employees’ perception of CSR are positively related to customer orientation and perceived performance. Perceived environmental CSR activities are the strongest variable to explain perceived performance whereas perceived ethical CSR activities are the strongest variable to determine customer orientation. Furthermore, customer orientation is positively related to perceived performance. Results provide fruitful insights for employee-based CSR and its possible positive consequences. Furthermore, the study intends to fill the research void in employee-based CSR and investigate its effect on marketing related outputs with its results.